2014
DOI: 10.1007/s11999-014-3690-y
|View full text |Cite
|
Sign up to set email alerts
|

CORR® ORS Richard A. Brand Award for Outstanding Orthopaedic Research: Engineering Flexor Tendon Repair With Lubricant, Cells, and Cytokines in a Canine Model

Abstract: Background Adhesions and poor healing are complications of flexor tendon repair. Questions/purposes The purpose of this study was to investigate a tissue engineering approach to improve functional outcomes after flexor tendon repair in a canine model. Methods Flexor digitorum profundus tendons were lacerated and repaired in 60 dogs that were followed for 10, 21, or 42 days. One randomly selected repair from either the second or fifth digit in one paw in each dog was treated with carbodiimide-derivatized hyalur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 37 publications
(55 reference statements)
1
54
0
Order By: Relevance
“…Canine, and rabbit studies have demonstrated both the intrinsic and extrinsic healing ability of flexor tendons 5,6 , the importance of early controlled passive motion in minimizing adhesion formation, relative to immobilization 7 , as well as the effects of different suture patterns on the healing process 8,9 . In addition, the canine model has been useful in testing translational tissue-engineering approaches to improve healing 10 . However, there are several important advantages in using a murine model relative to a large animal model including the relative cost, availability of murine specific reagents, and the ease of generating global knock-outs or tissue-specific deletion/overexpression constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Canine, and rabbit studies have demonstrated both the intrinsic and extrinsic healing ability of flexor tendons 5,6 , the importance of early controlled passive motion in minimizing adhesion formation, relative to immobilization 7 , as well as the effects of different suture patterns on the healing process 8,9 . In addition, the canine model has been useful in testing translational tissue-engineering approaches to improve healing 10 . However, there are several important advantages in using a murine model relative to a large animal model including the relative cost, availability of murine specific reagents, and the ease of generating global knock-outs or tissue-specific deletion/overexpression constructs.…”
Section: Introductionmentioning
confidence: 99%
“…72,73 The canine Zone II FDP tendon repair surgical model allows direct testing of surgical modifications and biological approaches before performing clinical trials in humans. 24,25,43,48,7476 …”
Section: Animal Modelsmentioning
confidence: 99%
“…37,39,45,47,48,81 By introducing cells into the paucicellular intrasynovial flexor tendon milieu and inducing a developmental paradigm between the repaired tendon ends, biological approaches attempt to accelerate healing and regenerate normal tissue. Multipotent MSCs from a variety of adult tissues have an excellent capacity to differentiate into the relevant tissue-specific phenotype and to provide potent immunosuppressive and anti-inflammatory effects.…”
Section: Biologic Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al showed that, Sox9 gene was not only able to promote the healing, but also increased the biomechanical strength at tendon-bone healing interface into an established bone-tendon healing model in rabbits (the long digital extensor tendon was detached from the lateral femoral condyle, and the free end of the tendon was inserted into a tunnel drilled into the proximal tibial metaphysis) [ 56 ]. In addition the recombinant Sox9 delivered by adenoviral vector can be expressed at a high level in the damaged tissues of the bone-tendon junction, which can stimulate the production of type II collagen and improve the healing [ 55 ]. In a rabbit model, Lattermann et al designed a study by inserting fl exor digitorum longus tendon into the calcaneus and applied gene delivery to the healing tendon insertion site.…”
Section: Different Treatment Modalities In Tendon-bone Interface Healingmentioning
confidence: 99%